1988
DOI: 10.1159/000116253
|View full text |Cite
|
Sign up to set email alerts
|

Fisher’s Syndrome Associated with <i>Campylobacter jejuni </i>Infection

Abstract: A patient developed typical features of Fisher’s syndrome after an infection with Campylobacter jejuni as ascertained by positive serology both in the blood and spinal fluid. This may be the first case of this association described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…The pathogenesis of GBS after CJC infection is not clear. No special serotype of CJC has been linked to GBS, and a GBS variant such as the Fisher syndrome has also been described following CJC infection [91]. Furthermore, GBS has occasionally been described after other enteric infections such as Yersinia [44] and Salmonella [155].…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of GBS after CJC infection is not clear. No special serotype of CJC has been linked to GBS, and a GBS variant such as the Fisher syndrome has also been described following CJC infection [91]. Furthermore, GBS has occasionally been described after other enteric infections such as Yersinia [44] and Salmonella [155].…”
Section: Discussionmentioning
confidence: 99%
“…Poliovirus infection is not a cause 19 . Campylobacter jejuni infection often with diarrhoea is the most common identifiable infectious precedent of GBS, particularly with the Miller-Fisher variant 15 2025. Mycoplasma pneumoniae also remains an important antecedent infection responsible for GBS 2629.…”
Section: Pathophysiologymentioning
confidence: 99%
“…Miller-Fisher syndrome (MFS) is a neuropathy associated with ataxia, areflexia, and ophthalmoplegia and is considered to be an infrequent variation of the more common form known as Guillain-Barré syndrome (GBS) (19). Renewed interest in the etiology of these neuropathies has stemmed from the findings that the onset of both MFS and GBS in some patients is preceded by intestinal infections with Campylobacter jejuni (10,12,18,20,24,25). Kuroki et al (11) reported in a study of 11 GBS patients that 7 of the 8 who were cultured were positive for C. jejuni and that 5 of the 7 experienced abdominal pain or diarrhea or both 5 to 15 days before onset of GBS symptoms.…”
mentioning
confidence: 99%